Investigating integument alterations in cubicle housed dairy cows: which types and locations can be combined?. (6th July 2015) - Brenninkmeyer, C.; Dippel, S.; Brinkmann, J.; March, S.; Winckler, C.; Knierim, U.
Abstract : In this study, a data set of 2922 lactating dairy cows in a sample of 64 conventional and organic dairy farms with Holstein Friesian cows in Germany and 31 conventional dairy farms with the dual purpose breed Fleckvieh in Austria was used to screen for correlations between the occurrences of different integument alterations. All cows were housed in cubicle systems. Alterations were classified as hairless areas (H), scabs or wounds (W) or swellings (S) and assessed at 15 locations of the cows' body. Highest median farm prevalences were found at the joints of the legs, which are already commonly included in studies on integumentary alterations: median farm prevalence was 83% for S and 48% for H at the carpal joints, followed by H (38%) and S (20%) at the lateral tarsal joints and H at the lateral calcanei (20%). Additional body parts with notable median prevalences for H were the hip bones (13%), pin bones (12%) and sacrum (11%). Three cluster models, with 2, 5 and 14 clusters, were built by hierarchical clustering of prevalences of the 30 most relevant alteration location combinations. Clustering revealed that location overruled type of lesion in most cases. Occasionally, clusters represented body segments significantly distant from each other, for example the carpal joints and lateral and dorsal calcanei. However, some neighbouring areas such as the medial and lateral hock area should be analysed separately from each other for causal analysis as they formed distinct clusters.